Clinical characteristics of complete responders versus non-complete responders to omalizumab, benralizumab and mepolizumab in patients with severe asthma: a long-term retrospective analysis - Maria Basagaña; Carlos Martínez-Rivera; Clara Padró; Ignasi Garcia-Olivé; Mimar Martínez-Colls; Juan Navarro; Laura Pardo; Paula Cruz; Gloria Cardona Peitx; Lídia Carabias; Albert Roger; Jorge Abad; et al. (Annals of Medicine, 2024)
AbstractBackground Some patients with severe asthma may benefit from treatment with biologics, but evidence has been mostly collected from randomized controlled trials (RCTs), in which patients’ characteristics are different from those encountered in asthma patients in the real-world setting. The aim of this study was to describe the clinical features of complete responders versus non-complete responders to long-term treatment with biologics in patients with severe asthma attended in routine daily practice.Methods Data of a cohort of 90 patients with severe asthma who were treated with biologics (omalizumab, benralizumab, and mepolizumab) for at least 12 months and were followed up to March 2022. Data recorded included clinical characteristics and effectiveness of treatment (exacerbation, Asthma Control Test [ACT] score, lung function, use of maintenance oral corticosteroids [mOCS]), FeNO, and blood eosinophils at baseline, at 12 months, and at the end of follow-up. Complete response is considered if, in addition to not presenting exacerbations or the use of mOCS, the ACT score was >20 and, the FEV1 >80% predicted.Results An improvement in all asthma control parameters was observed after 12 months of treatment and a mean follow-up of 55 months. After 12 months of treatment 27.2% of patients met the criteria of complete response and this percentage even increased to 35.3% at the end of follow-up. Long-term complete response was associated to better lung function with mepolizumab and omalizumab treatment and to less previous exacerbations in the benralizumab group. The main cause of not achieving a complete response was the persistence of an airflow obstructive pattern.Conclusions This study shows that omalizumab, benralizumab, and mepolizumab improved the clinical outcomes of patients with severe asthma in a clinic environment with similar effect sizes to RCTs in the long term follow-up. Airflow obstruction, however, was a predictor of a non-complete response to biologics.